Experimental evaluation of the light sword lens performance with a variable pupil size - Torres-Sepúlveda, Walter; Mira-Agudelo, Alejandro; Barrera, John Fredy; Kolodziejczyk, Andrzej (Photonics Letters of Poland, 2018)
This paper presents an experimental study designed to test the performance of the light sword lens (LSL) with different pupil sizes. To do so, Snellen optotype images obtained by a monofocal lens either with or without an LSL, were compared. Images were obtained for three different pupil sizes at several target vergences. The correlation coefficient and through-focus curves were obtained and compared. The experimental results show differences in the contrast and the depth of focus with different pupil sizes using the monofocal lens without an LSL. In contrast, when using the monofocal lens in combination with the LSL, the quality of the images is similar for all pupils and target vergences used, with slight differences only in halos and contrast. Full Text: PDF References G. Mikula, Z. Jaroszewicz, A. Kolodziejczyk, K. Petelczyc, M. Sypek, G. P. Agrawal, "Imaging with extended focal depth by means of lenses with radial and angular modulation", Opt Express 15, 9184, (2007). CrossRef A. Kolodziejczyk, S. Bará, Z. Jaroszewicz, M. Sypek, "The Light Sword Optical Element—a New Diffraction Structure with Extended Depth of Focus", J. Mod Opt. 37, 1283, (1990). CrossRef K. Petelczyc et al, "Presbyopia compensation with a light sword optical element of a variable diameter", Photonics Lett. Pol. 1, 55 (2009). DirectLink A. Mira-Agudelo et al, "Compensation of Presbyopia With the Light Sword Lens", Invest Ophthalmol Vis Sci 57, 6871, (2016). CrossRef R.A. Fisher, Statistical Methods for Research Workers (New York, Hafner, 13th Ed., 1958) CrossRef